Epirrita pulchraria (Taylor, 1907) transferred to Malacodea, with notes on the phylogeny and ecology of the tribe Operophterini (Lepidoptera: Geometridae: Larentiinae) - Truuverk, Andro; Õunap, Erki; Tammaru, Toomas (Zootaxa, 2017)
The Nearctic Epirrita pulchraria (Taylor, 1907) was revealed as a sister taxon of the Palaearctic Malacodea regelaria Tengström,1869 in a molecular phylogenetic analysis of the tribe Operophterini. DNA sequence variation in one mitochondrial (COI) and eight nuclear (28S, EF-1α, WGL, GAPDH, RPS5, IDH, MDH, CAD) gene fragments was used in the analysis. Bayesian inference resulted in a well-resolved phylogenetic hypothesis. According to the recovered phylogeny a new combination is proposed: Rachela pulchraria Taylor, 1907 is transferred from Epirrita Hübner, 1808 to Malacodea Tengström, 1869 as Malacodea pulchraria (Taylor, 1907) comb. nov. Larvae of both M. pulchraria and M. regelaria feed on coniferous trees, which distinguishes them from other members of the tribe. Close relatedness of M. pulchraria and M. regelaria is also supported by our study of male genital morphology. Ambiguous phylogenetic affinities of Epirrita viridipurpurescens (Prout, 1937) are discussed.